Molecular docking studies on the interaction of the Cryptosporidium parvum proteins, lactate dehydrogenase (LDH) and calcium-dependent protein kinase-1 (CpCDPK1), with selected plant compounds - Samson, Ivan Gregg O. (Animo Repository, 2024)
Lactate dehydrogenase (LDH) and calcium-dependent protein kinase-1 (CpCDPK1) are proteins involved in the life cycle and pathogenicity of Cryptosporidium parvum, the protozoan parasite that causes waterborne gastrointestinal disease in humans and animals. LDH is for the energy production of the parasite especially during its sporozoite and merozoite life stages while CpCDPK1 is for the regulation of invasion, egress, and development. Aloe vera, Ehretia microphylla, Blumea balsamifera, Zingiber officinale, and Thymus vulgaris are plants that have been used in folk medicine due to their antimicrobial properties. In this study, an in silico approach was used to predict the interactions between compounds from these plants against the LDH and CpCDPK1 proteins. Molecular dynamics RMSD analysis and molecular docking were performed. First, the structures of the proteins and ligands were obtained from RCSB Protein Data Bank and PubChem. Then, the stable conformations of the proteins before docking were predicted using COARE and Gromacs-2023.3. Prior to docking, the RMSD graphs confirmed the stabilization of the proteins at 40000 ns. To obtain the predicted binding affinities, Autodock Vina was used. Consequently, Discovery Studio Visualizer was utilized to visualize the predicted interactions. Ehretianone from E. microphylla and aloin from A. vera are predicted to have the strongest binding affinities with LDH (-7.8 kcal/mol) and CpCDPK1 (-8.6 kcal/mol). The predicted interactions involved among all the ligands are van der Waals, conventional hydrogen bonds, carbon-hydrogen bonds, alkyl and pi-alkyl bonds, pi-sigma bonds, pi-pi T-shaped bonds, pi-cation bonds, pi-anion bonds, amide-pi stacked bonds, and unfavorable acceptors and donor bonds. These predicted interactions may be useful in considering the plant sources for their potential as anti-cryptosporidial drugs. In vitro and in vivo studies must be conducted to establish a better understanding of these interactions.